The effect of a curruption scandal, recession and legislation on voluntary disclosure, reporting quality, and governance, compliance and control: the case of Brazil. - Whitehead, Martin (Cranfield University, 2019)
This thesis sets out the results of a mixed methods research project comprising three separate studies that look to address the overarching research question: how do trigger events in the form of crises and legislation affect (i) corporate reporting, i.e. through voluntary disclosure and earnings management, and (ii) governance, compliance and internal controls? This important topic, which sits at the intersection of three research domains - crisis management; corporate control and governance; and financial reporting quality - has not been targeted in a holistic way in prior studies. This thesis aims to shed new light on the topic by addressing this gap. Paper 1 comprises a systematic literature review (SLR) which is motivated by the research question: - how do crisis trigger events (corruption scandal, transparency legislation, and recession) impact corporate responses in the form of management actions, and their reporting choices around voluntary disclosure and earnings management? Adopting established SLR methodology, the review identifies 91 articles from research domains across management, accounting and finance. The study synthesizes key findings from the sample, identifies emergent themes, and constructs a conceptual crisis response framework centred on dynamic stakeholder management for determining action and reporting choices, which must be navigated within a control and regulatory environment that chiefly influences reporting response options. The paper also sets out implications for practitioners and policy makers, makes the case for Brazil as a fruitful location for relevant and interesting studies, and presents a tangible research agenda which is used to inform Papers 2 and 3. Paper 2 is a case study which examines how Petrobras responded to a major corruption scandal in the period 2010-2017 through (i) disclosures in its annual report (AR), sustainability report (SR), and press releases; and (ii) organizational restructuring changes made to strengthen governance and controls in response to the crisis. We find evidence in support a legitimacy theory explanation of a strategy to repair trust with key stakeholders through (i) enhanced disclosure and (ii) an evolving sequence of actions to regain control and restructure the organization, pursuant to trust repair models. In addition, we obtained new insights into how a company uses the AR and SR to target different stakeholder groups and communicate differently with them to manage their respective legitimacy concerns, findings which support stakeholder theory and organizational façade theory explanations. Finally, our review of actions taken by management shows that these align well with models of trust repair and legitimacy management, and appear to have resulted in Petrobras successfully regaining legitimacy by 2017. Paper 3 is a quantitative study which assesses how three major external events influenced earnings management in Brazil during the period 2000 – 2017. We consider the effect of the Petrobras corruption crisis, recession, and the introduction of a new transparency law (the Brazil Clean Company Act (BCCA)). We find that the corruption crisis affecting Petrobras in 2014 and 2015 (and the resulting external scrutiny from regulators, media and the public associated with it), was of such an intensity that it had an impact similar to that of legislation elsewhere, such as Sarbanes-Oxley: - i.e. in Brazil during the corruption crisis the level of accruals-based earnings management (AEM) decreased and real earnings management (REM) increased as the two were used as substitutes. During recession, firms reduced the level of REM they use, which is consistent with an interpretation that this costly form of manipulation is not required when all firms are facing unfavourable reporting. BCCA, which was introduced in 2014 to improve transparency and reduce corruption, has had the effect of reducing real earnings management, which we interpret as being due to an increased focus on compliance and governance with improved tone at the top. This study is the first to consider the impact of both a corruption crisis and transparency legislation on earnings management behaviour, and adds to extant knowledge on what influences REM usage, the results of which widen our understanding of how management weighs the costs and benefits of its manipulation options, dependent on external scrutiny and the quality of internal governance mechanisms Overall, the results from the three papers enable us to contribute to the research literature in a number of ways in respect of the influence specific crisis and exogenous shock events have on management decision making related to (i) its responsive actions to ensure the adequacy of its governance and controls environment, and (ii) in the reporting and communication choices it makes around earnings management and voluntary disclosure; findings which have relevance beyond the Brazilian environment.
Keywords: Anti-corruption; crisis management; earnings management; Lava Jato; legitimacy; organizational facades; trust repair; stakeholder analysis; voluntary disclosure